EFFECT OF PHOSPHATE FERTILIZATION ON GROWTH, YIELD AND SEED PHOSPHORUS CONTENT OF BAMBARA PEA (VIGNA SUBTERRANEA) L AND RACES - N. C. Temegne; V. D. Taffouo; T. C. Tadoh; W. F. Gouertoumbo; G. A. Wakem; F. T. D. Nkou; P. P. K. Nuemsi; E. Youmbi (Journal of Animal and Plant Sciences, 2019)
Responses of three Bambara pea [Vigna subterranea (L.) Verdc.] landraces subjected to different phosphorus (P) levels (0, 50, 100, 150 and 200 kg P2O5.ha-1) were investigated in research farm during the years 2015 and 2016 at Mendong and Soa districts (Cameroon). Treatments were arranged factorial completely randomized design with three replications. Some growth (shoot length, number of branches) and yield (seed diameter, number of pods plant-1, pods weight plant-1, seeds weight plant-1, 100-grain weight and grain yield) parameters and seed P content were determined. P application led to a significant increase in all growth and yield parameters and seed P content in both years with the high values at 150 kg P2O5.ha-1 compared to control. The maximum grain yield (1.99 t ha-1) was found in White Seed Coat with grey eyes (WSCge), which was statistically similar to White Seeds Coat (WSC) (1.85 t ha-1) in 2015. Light Red Seed Coat (RSC) had the least grain yield (1.23 and 0.71 t ha-1) during 2015 and 2016, respectively. WSCge and WSC can be cultivated successfully in the humid forest agro-ecological zone. A dose of 150 kg P2O5.ha-1 can be considered as the efficient fertilizer to improve significantly the Bambara pea growth and yield performance.
Keywords: phosphate fertilizer; productivity; seed phosphorus content; Vigna subterranea